Maruina guria (Diptera, Psychodidae), a new psychodid species from Brazil - Bravo, Freddy (Zootaxa, 2004)
Maruina guria sp. nov. is described from Serra do Cip , Minas Gerais State, Brazil. This new species is the first record of the subgenus Aculcina Hogue from Brazil. Some comments are presented concerning the two subgenera of Maruina M ller.